2004
DOI: 10.1097/01.ta.0000141332.43183.7f
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Distress, Alcohol Disorders, and Recurrent Trauma Across Level 1 Trauma Centers

Abstract: High levels of posttraumatic distress, recurrent trauma, and alcohol abuse/dependence were present in more than half of acute care inpatients. Early mental health screening and intervention procedures that target both PTSD and alcohol use should be developed for acute care settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 33 publications
4
54
2
Order By: Relevance
“…51 The Harborview pilot study tested an early combined intervention that included continuous master's level case management over the first six months post-injury and evidence-based medication and psychotherapy for PTSD delivered by MD/PhD mental health specialists. As with the pilot study, inclusion criteria for the Harborview pilot remained extremely broad.…”
Section: Larger Scale Randomized Effectiveness Trials Of Collaborativmentioning
confidence: 99%
See 4 more Smart Citations
“…51 The Harborview pilot study tested an early combined intervention that included continuous master's level case management over the first six months post-injury and evidence-based medication and psychotherapy for PTSD delivered by MD/PhD mental health specialists. As with the pilot study, inclusion criteria for the Harborview pilot remained extremely broad.…”
Section: Larger Scale Randomized Effectiveness Trials Of Collaborativmentioning
confidence: 99%
“…2,24,33 Physical injury as the result of a traumatic event increases the risk for experiencing psychiatric symptoms, including depression and post-traumatic stress disorder (PTSD), as well as other psychosomatic symptoms, or those without any known medical cause. 6,8,10,11,18,13,20,22,43,48,51,52,54,49 In analysis of data from the National Study on the Costs and Outcomes of Trauma (NSCOT), the largest study to date assessing functional and work outcomes after an injury, researchers found that 23 percent of injury survivors were continuing to experience PTSD symptoms a year post-injury. 55 In addition, research indicates between 20-50% of trauma patients on surgical wards fit criteria for current or long term substance abuse.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations